Norma Peralta. the Story of a Pioneer of the Accounting Academy in Chile - Restrepo-Quintero, K (John Wiley and Sons Inc, 2025)
The literature on gender and accounting has focused on the participation of women in the accounting profession, documenting the barriers to entry, the problems of professional promotion, and issues related to gender roles, which shows a lack of historical works that narrate the life experiences of women within the accounting academy, particularly in Chile. Therefore, the purpose of this work is to tell the story of Professor Norma Peralta, who was one of the first women to graduate from undergraduate studies and enter the accounting academy in the case of the Universidad Santiago de Chile (USACH). This work of historical reconstruction gathered information through various conversations with Norma and interviews that have documented her passage through the academy from its beginnings until her retirement from her Alma Mater, which helps to show the contribution in the field of accounting education made by this pioneer. © 2025 John Wiley & Sons Ltd.